Effect of Vacuum Drying in Target Preparation from Potassium Hydroxide Solution on the Spectra of Rutherford Backscattering Spectroscopy. (May 2015) - Toriyama, T.; Suzuki, S.; Kawasaki, K.; Takagi, Y.; Nagai, M.; Fukuda, H.; Kondo, K.; Oguri, Y.
Abstract: In order to measure the amounts of fluorine (F) atoms in the off-gas drain from polymer electrolyte fuel cells (PEFCs) using proton Rutherford Backscattering Spectroscopy (p-RBS), we used an impinger where potassium hydroxide (KOH) solution (0.1 mol/L) was filled and prepared the targets for p-RBS using these samples. In the measured RBS spectrum, however, the peak of fluorine (F) atoms of the decomposition products could not be clearly observed due to the interference by the low energy tail of the potassium (K) atom's peak. We confirmed using SEM, EPMA and XRD that the origin of the low energy tail of the potassium (K) atom's peak was the absorption of carbon dioxide (CO2 ) in the air by potassium hydroxide (KOH) solution during drying. We also found that the target prepared by vacuum drying was more suitable for measuring the spectra of light elements in p-RBS than that by natural drying.